77 Impact of Cardiovascular Comorbidities on Mortality Amongst Psychiatric Patients in the United Kingdom. (3rd June 2016) - Carter, Paul R; Carter, Andrew; Reynolds, Jennifer; Uppal, Hardeep; Chandran, Suresh; Potluri, Rahul
Abstract : Introduction: Cardiovascular disease is increasingly being associated with novel risk factors including psychiatric diseases. Although a high prevalence of cardiovascular comorbidities has been demonstrated in psychiatric patients, the impact of these on mortality are yet to be studied. Objectives: We aimed to investigate the prevalence of cardiovascular comorbidities and their contribution to mortality amongst psychiatric patient in North England, UK. Methods: Anonymous information on adult psychiatric patients was obtained from hospitals in North England, UK between 1 st January 2000 and 31 st March 2013. This data was analysed according to the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) study protocol. ICD-10 and OPCS-4 codes were used to trace patients coded for psychiatric disease, demographics, prevalence of cardiovascular comorbidities and mortality data. Mortality of psychiatric patients with and without cardiovascular comorbidities were compared by logistic regression. P values <0.05 were taken as statistically significant. Results: Amongst 929552 patients admitted during the study period, 80172 had a diagnosis of psychiatric disease. Mean age of psychiatric patients was 53.9 years, 50.8% were male and 84.0% were Caucasian. 22679 (28.3%) psychiatric patients died. Logistic regression showed mortality was increased significantly by comorbid diagnoses of ischaemic heart disease (OR 1.221), atrial fibrillation (OR 1.357), cerebrovascular disease (OR 1.657), heart failure (OR 2.555), ischaemic stroke (OR 1.386), myocardial infarction (OR 1.234), peripheral vascular disease (OR 1.581), type 1 diabetes (OR 1.836) and type 2 diabetes (OR 1.171). Conversely mortality was significantly reduced in psychiatric patients with comorbid hypertension (OR 0.630), hyperlipidaemia (OR 0.416) and angina (OR 0.779). Conclusion: We have demonstrated that cardiovascular comorbidities are highly prevalent amongst psychiatric patients and contribute significantly to mortality. We also demonstrate that diagnoses of some cardiovascular risk factors (hypertension and hyperlipidaemia, but not diabetes) has a protective effect on mortality, probably due to effective monitoring and management of risk factors. Improved management of cardiovascular risk amongst psychiatric patients could prevent mortality in this at-risk group.